A Decade of Research on Employee Perfomance and Leadership: A Bibliometric Synthesis from Scopus (2014-2024) - Adawiah, Andi (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study maps the intellectual architecture surrounding Transformational Leadership, Competence, Work Motivation, Organizational Culture, and allied constructs across a decade of scholarly discourse (2014–2024). Through the dissection of 318 Scopus-indexed articles via VOSviewer, it unveils patterns of collaboration, thematic prominence, and lacunae in the literature. Notably, scholarly fervor peaked between 2017 and 2020, only to taper markedly by 2024—a curious attenuation worth reflection. While perennial topics—performance and satisfaction—dominate the canon, emergent themes such as mental health, innovation, and sustainability linger at the periphery. This bibliometric lens offers researchers a compass to navigate future inquiry and urges HR practitioners to reconsider the epistemic weight behind the models they borrow. In a field enamored with frameworks, this study reminds us that even theoretical orthodoxy benefits from a periodic audit.